2021
DOI: 10.1016/j.intmar.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Buying a New Product with Inconsistent Product Reviews from Multiple Sources: The Role of Information Diagnosticity and Advertising

Abstract: Product reviews are critical high-scope non-marketing cues for consumers to obtain useful product information from various perspectives. However, the effects of inconsistent reviews among multiple sources on new product sales are underexplored. Based on the cue-diagnosticity framework, this research investigates how multi-source review inconsistency (MSRI) affects purchase intention and new product sales in the context of the U.S. automobile industry when firms signal product quality through advertising as a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…Therefore, the discrepancy in the valence of online reviews (from previous beliefs) and inconsistencies between positive and negative views will interfere with consumers' acceptance of online information (Reimer and Benkenstein, 2016). Consequently, review valence is vital in determining review diagnosticity (Byun et al, 2021), as it generates different interpretations and attributions from consumers (Qiu et al, 2012). It is also important to acknowledge that, in seeking to comply with social norms, people tend to give positive comments and reviews about others, making positive comments less informative and less reliable relative to negative reviews (Qiu et al, 2012).…”
Section: Online Review Valencementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the discrepancy in the valence of online reviews (from previous beliefs) and inconsistencies between positive and negative views will interfere with consumers' acceptance of online information (Reimer and Benkenstein, 2016). Consequently, review valence is vital in determining review diagnosticity (Byun et al, 2021), as it generates different interpretations and attributions from consumers (Qiu et al, 2012). It is also important to acknowledge that, in seeking to comply with social norms, people tend to give positive comments and reviews about others, making positive comments less informative and less reliable relative to negative reviews (Qiu et al, 2012).…”
Section: Online Review Valencementioning
confidence: 99%
“…Online review diagnosticity refers to the adequacy of information provided in the review in facilitating the generation of solutions for a task (Qiu et al, 2012). In extant research, online review diagnosticity is often equated with the reliability of the review in distinguishing product alternatives (Byun et al, 2021). The cue-diagnosticity theory advocates that consumers are exposed to various cues in the shopping process, including advertisements, prices and online reviews.…”
Section: Online Review Diagnosticitymentioning
confidence: 99%
“…Broadcasters also issue timely responses to consumers, providing them with highly personalized product recommendations, guidance and services (Sun et al , 2019). Consumers’ assessments of the level of information provided by marketers influence their purchase decisions (Byun et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the impact of consistency across review information, the prior literature shows that a set of review information that varies in terms of valence (Park and Jun, 2018;Zhang et al, 2014), breadth of information (Qiu et al, 2012;Xu, 2021) or review source (Byun et al, 2021) can influence customers' perceptions of how helpful (Yin et al, 2016) or credible (Qiu et al, 2012) the reviews are. For instance, Purnawirawan et al (2012) found that customers tend to consider reviews more useful when there is consistency across the valence of review ratings.…”
Section: 2mentioning
confidence: 99%
“…, 2014), breadth of information (Qiu et al. , 2012; Xu, 2021) or review source (Byun et al. , 2021) can influence customers' perceptions of how helpful (Yin et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%